Ghost in the Shell? The Philosophy of Artificial Intelligence by Miyake Yōichirō. - Nishiyama, Takahiro (Vienna Journal of East Asian Studies, 2023)
Miyake Yōichirō, an engineer who creates artificial intelligence (AI) for characters in computer games, asserts that current AI technology is rooted in Western philosophical traditions. He argues that when Western AI was created it was not generally acknowledged as intelligent in its own right. It is therefore subjected to verification tests, such as the Turing test, and only if it passes these does it qualify as intelligent. However, Miyake points out that the goal of an AI engineer is to humanise AI by giving it desires and worries. He claims that it is necessary to merge Eastern and Western thought in the design process in order to achieve a more human-like holistic AI. Consequently, the configuration of AI in computer games depends on the perception of the nature of human intelligence held by the game designer. This article examines Miyake's philosophical approach in defining and producing AI, and how the AI of computer game characters is influenced by the software developer's view of human beings.